Determinants of household debt in Malaysia / Nur Ain Najwa Zainal and Nur Adilla Omran - Zainal, Nur Ain Najwa; Omran, Nur Adilla (Faculty of Business and Management, 2018)
The issue of household debt is at critical stages which need to overcome before it may cause into the financial crisis so that the fluctuation of the household debt level needs to be determined even there is show decreasing for 2016 to June 2018. This study is using the time series data to achieved the objective of this study is to identifying the macroeconomic variables relationship with household debt especially in Malaysia. This study is used the Multiple Linear Regression (MLR) model to see the relationship between the household debts with the macroeconomic variables which are inflation rate, interest rate, saving level and unemployment. The findings for this study shows that, interest rate are the most significant variable that could effect on the household debt level in Malaysia followed by saving level and unemployment level. Moreover, there are shows positive relationship for saving level and unemployment level towards household debt in Malaysia. This is show that the higher the saving level, the higher the level of household debt and the higher the unemployment rate, the higher the household debt in Malaysia. On the other hand, this study found that interest rate is a negative relationship with household debt in Malaysia while inflation rate is insignificantly related with dependent variable, household debt in Malaysia. All the data from this study are collected from Datastream which subscribed from UiTM and by looking at monthly basis from year January 2008 until June 2018 with 126 observations.